Hyperthermia Management Using Tepid Sponging to Reduce Body Temperature in Children With Typhoid Fever in the Emergency Department - Kartini Abd Malik; Fitria Fitria; Haeril Amir; Rahmat Hidayat (PT.Mantaya Idea Batara, 2025)
Typhoid fever is a systemic infectious disease caused by Salmonella enterica serovar Typhi and remains a major public health concern in many developing countries, including Indonesia. The disease is primarily transmitted through the consumption of contaminated food or water. Management of fever involves both pharmacological and non-pharmacological approaches, one of which is tepid sponging. This paper aims to describe the effectiveness of tepid sponging in reducing body temperature among pediatric patients with typhoid fever. A case study was conducted on a pediatric patient (An. Z) diagnosed with typhoid fever. The non-pharmacological intervention—tepid sponging—was applied using a holistic nursing process, including assessment, diagnosis, intervention, implementation, and evaluation. The findings indicate that the patient’s initial body temperature was 39.0°C, which decreased to 37.8°C following the intervention. These results demonstrate the effectiveness of tepid sponging in lowering body temperature in children with typhoid fever. In conclusion, tepid sponging is an effective non- pharmacological nursing intervention for reducing fever in pediatric typhoid patients. These findings offer important clinical implications for nurses, particularly in emergency departments, as a supportive measure to improve patient comfort and facilitate recovery.